PENGARUH STRUKTUR ASET, LIKUIDITAS, PROFITABILITAS, KEBIJAKAN DIVIDEN, KEPEMILIKAN SAHAM INSTITUSIONAL DAN RISIKO BISNIS TERHADAP KEBIJAKAN UTANG (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2015-2017) - Benedicta Agustine Kusumi; Chermian Eforis (Universitas Multimedia Nusantara, 2020)
The purpose of this research is to obtain the empirical evidence about the effect of the asset structure, liquidity measured by current ratio, profitabilty measured by return on asset, dividend policy measured by dividend payout ratio, institutional’s ownership and business risk toward debt policy. The sample in this research was selected using purposive sampling method and the secondary used in this research was analyzed using multiple regression method. The total amount of sample in this research were 30 firms which have been registered as manufacture sector in BEI simultaneously for the year 2015-2017, published financial statements as the end of 31 December and had been audited, used Rupiah as currency, had a positive net income, payment cash dividend, did not do corporate action, specifically: share split, reverse split, right issue, and treasury share, had issues institutional’s ownership. The result of this research were (1) asset structure, liquidity, and institutional ownership have significant negative effect towards debt policy, (2) profitability has significant positive effect towards debt policy, (3) dividend policy and business risk has no significant effect towards debt policy Keywords: Asset Structure, Business Risk, Debt Policy, Dividend Policy, Institutional’s Ownership, Liquidity, Profitability